A case study on improving essay writing tasks - Shuaib, Farid Sufian (2011)
: From the experience of law lecturers, essay writing assignment for law students has been besotted with problem of plagiarism or lack of originality. Presented with a question on a particular topic in a law subject, students tends to take the easy way out by simply collating relevant sections from several textbooks on the subject matter and present it as an original legal essay. The essay writing task also suffers from summative format where most students have no prior discussion with instructor on the expected particulars result of the essay writing. In semester 2 of year 2010/2011 session, a new format assigning essay writing was adopted by the author. Among new elements in assigning the task: students are required to prepare a re-port in a group; the report must include a field work; and the groups are required to submit and to discuss with the instructor their draft report before its final submission. This paper seeks to discuss the experience of the author in adopting this new format in improving the teaching and learning experience of law students including the rationale, the problem and the perceived benefit of this new method.